A review of brain circuitries involved in stuttering - Craig-McQuaide, Anna; Akram, Harith; Zrinzo, Ludvic; Tripoliti, Elina (Frontiers in Human Neuroscience, 2014)
Stuttering has been the subject of much research, nevertheless its aetiology remains incompletely understood. This article presents a critical review of the literature on stuttering, with particular reference to the role of the basal ganglia. Neuroimaging and lesion studies of developmental and acquired stuttering, as well as pharmacological and genetic studies are discussed. Evidence that stuttering of structural and functional changes in the basal ganglia in those who stutter indicates that this motor speech disorder is due, at least in part, to abnormal basal ganglia cues for the initiation and termination of articulatory movements. Studies discussed provide evidence of a dysfunctional hyperdopaminergic state of the thalamocortical pathways underlying speech motor control in stuttering. Evidence that stuttering can improve, worsen or recur following deep brain stimulation (DBS) for other indications is presented in order to emphasise the role of basal ganglia in stuttering. Further research is needed to fully elucidate the pathophysiology of this speech disorder, which is associated with significant social isolation.